ASSESSMENT OF CUSTOMER SATISFACTION OF FINANCIAL ORGANIZATIONS (Revista Inclusiones, 2020)
The article comprises a set of theoretical and methodological statements and practical suggestions about the modern methods of assessment of customer satisfaction of financial organizations. The main quality control methods include surveys of costumers, collection of statistic data from a survey, mass questionnaires, observation, telephone interviews, personal in-depth interview, focus group, SERVQUAL model and Kano technique. But they all have their advantages and disadvantages discussed in the article.